The Protection of Creditors as Fiduciary Recipients in Debt Transfers Without Good Faith in Credit Agreements (Study of Decision Number 132/PID.B/2023/PN.SPG) - Riyanto, Rajwa Khaicirinu; Joesoef, Iwan Erar (Universitas Islam Sultan Agung, 2025)
One of the problems of a credit agreement is the transfer of debt (take over credit) underhand without the knowledge of the creditor as the fiduciary recipient. Therefore, this paper is conducted to analyze the protection for creditors as fiduciary recipients in the transfer of debt (take over credit) underhand without the knowledge of the creditor in one of the cases, namely Decision Number 132 / PID.B / 2023 / PN. Spg. This paper is a qualitative normative whose data collection uses literature studies and is analyzed using a statutory approach and a case approach. This study concludes that in the case of Decision Number 132 / PID.B / 2023 / PN.Spg, the debt transfer agreement (take over credit) between the debtor and a third party is invalid and null and void because it violates the objective principles in the terms of the agreement. The transfer of debt (take over credit) at PT Federal International Finance can be legal and in accordance with the law if it complies with the procedures determined by PT Federal International Finance as the creditor, one of which is by consulting and contacting and the agreement is known and approved by the creditor.